Audit Analytics in the Financial Industry - Dai, Jun (Rutgers Studies in Accounting Analytics Ser., 2019)
Split into six parts, contributors explore ways to integrate Audit Analytics techniques into existing audit programs for the financial industry. Chapters include topics such as fraud risks in the credit card sector, clustering techniques, fraud and anomaly detection, and using Audit Analytics to assess risk in the lawsuit and payment processes.